2017
DOI: 10.1002/tox.22395
|View full text |Cite
|
Sign up to set email alerts
|

The aflatoxin B1‐fumonisin B1 toxicity in BRL‐3A hepatocytes is associated to induction of cytochrome P450 activity and arachidonic acid metabolism

Abstract: Human oral exposure to aflatoxin B (AFB ) and fumonisin B (FB ) is associated with increased hepatocellular carcinoma. Although evidence suggested interactive AFB -FB hepatotoxicity, the underlying mechanisms remain mostly unidentified. This work was aimed at evaluating the possible AFB -FB interplay to induce genetic and cell cycle toxicities in BRL-3A rat hepatocytes, reactive oxygen species (ROS) involvement, and the AFB metabolizing pathways cytochrome P450 (CYP) and arachidonic acid (ArAc) metabolism as R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 64 publications
(151 reference statements)
1
10
0
1
Order By: Relevance
“…TiO 2 NPs stimulated the expression of CYP enzymes, such as Cyp4a14 and Cyp2b9. CYP enzymes expressed throughout the human body play a crucial role in human physiology and are involved in drug and xenobiotic metabolism as well as biosynthesis of endogenous molecules . During the CYP catalytic cycle, ROS is generated through uncoupling of the enzymatic cycle .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 NPs stimulated the expression of CYP enzymes, such as Cyp4a14 and Cyp2b9. CYP enzymes expressed throughout the human body play a crucial role in human physiology and are involved in drug and xenobiotic metabolism as well as biosynthesis of endogenous molecules . During the CYP catalytic cycle, ROS is generated through uncoupling of the enzymatic cycle .…”
Section: Discussionmentioning
confidence: 99%
“…19,20 In our experiments, Res relieved ER stress and ROS generation and CYP enzymes expressed throughout the human body play a crucial role in human physiology and are involved in drug and xenobiotic metabolism as well as biosynthesis of endogenous molecules. 21,22 During the CYP catalytic cycle, ROS is generated through uncoupling of the enzymatic cycle. 23 Two pathways exist within the CYP catalytic cycle, which can generate ROS without completion of substrate oxidation, a process known as "reaction uncoupling."…”
Section: Tio 2 Nps Induce Insulin Resistance and Elevation Of Plasmmentioning
confidence: 99%
“…It was reported that binucleated neuronal cells in the cortical region of the human brain in Alzheimer's disease showed severe oxidative stress (22,48). It was demonstrated that hepatocyte binucleation is induced by an increased production of ROS, reactive nitrogen species, and other free radicals, which cause significant oxidative DNA damage in hepatic cells (8,49,50). These results show that vitamin C might attenuate DEN-induced liver toxicity (Figure 4).…”
Section: Discussionmentioning
confidence: 82%
“…In the current study, we observed both a reduction of proliferation (Figure 1) as well as of cell viability ( Figure S1), thus assuming that cell cycle arrest in HepG2 and Huh7.5 cells is possible. Other authors further implied that FB1 significantly influences the expression of cytochrome P450, which in turn influences important functional pathways of HCC in vitro [46]. Yet, since FB1 is a mycotoxin with a well-known promoting role in HCC in vivo [23], further data are needed in order to decipher its mechanistic role in HCC pathogenesis.…”
Section: Discussionmentioning
confidence: 99%